Fully therapeutic laparoscopy for penetrating abdominal trauma in stable patients (2022)
We performed a retrospective study of PAT patients with hemodynamic stability who presented to 2 medical centers in Bogota Colombia between December 2018 and December 2019. All patients underwent to diagnostic with fully therapeutic laparoscopic surgical treatment. Our chart review included 192 patients with PAT. Patients who were hemodynamically unstable, partial or not fluid resuscitation responders, under 15 years of age were excluded. Twenty four patients met selection criteria and underwent initial laparoscopic evaluation with diagnosis and fully therapeutic laparoscopic definitive treatment. Sociodemogrphic, intraoperatory and postoperatoy variables were analyzed. The patients were evaluated by a multidisciplinary group of surgeons with training in laparoscopy and trauma surgery. The benefits, complications and the possible need of conversion to open surgery were explained to all patients and clearly exposed in the informed consent. The type of PAT was classified between a gunshot wound and stab wound. Intraoperatively, the therapeutic approach was defined after the initial damage assessment, the surgeon's expertise, the degree of contamination and the general condition of the patient.